NEW CONCEPT OF THE GEODYNAMIC NATURE OF THE DEVONIAN ORE-BEARING BASALT-RHYOLITE FORMATION IN RUDNYI ALTAI - Promyslova M.Yu. (My University, 2004)
It can be assumed that orebearing volcanosedimentary sequences of Rudnyi Altai began to form since the Emsian at the transition from the axial rift of the Ob-Zaisan ocean spreading to the continental rift of the Altai-Mongol block. Devonian riftogenesis was manifested only in Rudnyi Altai, neighboring areas of Gornyi Altai, and the entire central part of the Altai-Sayan fold system. This process involved a vast (over 2000-km-long and up to 200-km-wide) region [4] comparable in size to the Basin and Range Province in the western United States.
Keywords: Devonian; Paleozoic::Devonian; Палеозой::Девонская